Language Acquisition of English Vocabulary on 5 Years Old Child Through Social Media YouTube - Hernalia Citra Dewi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Language acquisition cannot just be acquired from birth. There is a process and stages in acquiring a language. Language is obtained because of the continuous practice factor. It is possible for someone who already has a mother tongue to have a second language (B2) which is used as a communication tool alongside the first language. Acquisition of a second language can be obtained through the influence of the environment or activities carried out continuously. This study will describe how the effect of viewing on social media YouTube affects the acquisition of a second language for a five years old girl. This research uses qualitative methods with descriptive explanations. The results of this study found that the subject's second language proficiency in English was evident from his understanding of the films and videos she had watched repeatedly. His mastery of a second language can also be seen in the ability of the subject to mention the objects around her, the names of fruits and animals, and to be able to make simple sentences in English.Keywords: Language acquisition, second language, YouTube.